What's African Countercult Apologetics? - Kajuma, Vincent; Adherent Apologetics (2020)
In this interview, I talk with Vincent Kajuma. Vincent Kajuma serves on staff at Emmanuel Baptist Church (Nairobi) and is the Kenya coordinator for the Centers for Apologetics Research. He is a leader apologist in the African countercults movement.
free